Polyindole modified g-C3N4 nanohybrids via in-situ chemical polymerization for its improved electrochemical performance - Verma C.J.; Keshari A.S.; Dubey P.; Prakash R. (My University, 2025)
In this work, surface modification of graphitic carbon nitride (g-C3N4) nanoflakes is achieved by polyindole (PIn) without using any surfactant via in-situ chemical polymerization. The electro capacitive properties of the materials are directly related to their surface functionalities, microstructure, and interfacial interaction. Therefore, the interface engineering of g–C3N4–PIn nanohybrid is performed to improve the electrochemical activity. The optimal composition of g–C3N4–PIn nanohybrids is investigated by varying amounts of indole monomer (5, 20 and 50 mg) with a fixed weight of g-C3N4 (10 mg) during polymerization. Various spectroscopic/microscopic techniques identify the as-synthesized nanohybrids before exploring their application as metal-free electrode material. In comparison (current density at 2 Ag−1), the 1:2 g–C3N4–PIn nanohybrid exhibits better electrochemical performance over the others. The specific capacitance (Cs) values are estimated as 115.8 Fg−1for 1:2 g–C3N4–PIn and 12.4, 38.7, 21.5, and 66.9 F g-1, for bare g-C3N4, pure PIn, and other two nanohybrids (1:0.5 and 1:5) of g–C3N4–PIn respectively. In this article, the 1:2 g–C3N4–PIn nanohybrid is an optimal weight ratio and advances in strategies on the metal-free and binder-free electrodes with the fast diffusion process of charges. It shows 96% cycling stability over 250 cycles. © 2020